Translator’s Visibility: A Linguistic Analysis of English Translations of the Holy Qur’an - Khan, Abdul Rafay; Kausar, Ghazala; Farooq, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Adorned in a matchless form, the all-encompassing, universal, and ever modern discourse of The Holy Qur’an has been testified as a linguistic miracle by its translators, interpreters, and researchers. Being ‘The Book’ addressed to whole mankind, its readers are speakers of different languages of the world. This wide readership has made the most widely translated text in the world. In this context, the task of the translator is to make certain shifts to bridge the linguistic gap between the source and the receptor languages. However, it demands a careful effort as he/she has to avoid any such linguistic shift that may change the message of the original. The present research endeavors to analyze the selected translations of The Holy Qur’an focusing on what translation adjustments/shifts have been made by the translators; how these adjustments make the translators visible in the translations?; and how different ideological and religious positions of the translators make them visible in their translations. Visibility here refers to the involvement of a translator in affecting the message of the source text. Nida and Taber’s model of translation analysis has been applied to analyze translation of ten selected verses of The Qur’an. Specifically, those verses are selected which are about The Holy Messenger Muhammad (S.A.W). The translations of Arberry, Dawood, and Shakir, who translated the holy text by adopting different adjustments, are studied. These translators belonged to the three major religions i.e Islam, Christianity, and Judaism. The analysis revealed that translators, at times adopt unnecessary translation shifts which make them visible in their translations, and their religious background influence them to adopt different techniques in translations.